CCND1 Amplification Contributes to Immunosuppression and Is Associated With a Poor Prognosis to Immune Checkpoint Inhibitors in Solid Tumors - Chen, Yu; Huang, Yingying; Gao, Xuan; Li, Yi; Lin, Jing; Chen, Lizhu; Chang, Lianpeng; Chen, Gang; Guan, Yanfang; Pan, Leong Kin; Xia, Xuefeng; Guo, Zengqing; et al. (Frontiers in Immunology, 2020)
CCND1 amplification relevant to malignant biological behavior exist in solid tumors. The prevalence and utility of CCND1 amplification as a biomarker for the clinical response to treatment with immune checkpoint inhibitors (ICIs) is unknown. We examined the prevalence of CCND1 amplification and its potential as a biomarker for the efficacy of ICIs therapy for solid tumors using a local database (n=6536), the TCGA database (n=10606) and the MSKCC database (n=10109). Comprehensive profiling was performed to determine the prevalence of CCND1 amplification and the correlation with the prognosis and the response to ICIs. A CCND1 amplification occurs in many cancer types, correlates with shorter overall survival, and with inferior outcomes with ICIs therapy. Transcriptomic analysis showed various degrees of immune cells exclusion, including cytotoxic cells, T cells, CD8+ T cells, DC cells and B cells in the tumor microenvironment (TME) in a TCGA CCND1 amplification population. The gene set enrichment analysis suggested that CCND1 amplification correlates with multiple aggressive, immunosuppressive hallmarks including epithelial mesenchymal transition, TGF-β signaling, KRAS signaling, PI3K/AKT/mTOR signaling, p53 pathway and hypoxia signaling in solid tumors. These findings indicate that CCND1 amplification may be a key point related to immunosuppression in TME and multiple malignancy hallmarks, and it hinders not only the natural host immune responses but also the efficacy of ICIs.